P-47 Building sustainability from the bottom up: the importance of strong system relationships to support strategic success. (19th November 2022) - Heaps, Kate; Devlin, Jon
Abstract : Background/Aims: The Health and Care Act 2022 includes a legal duty to 'specifically require Integrated Care Boards to commission services or facilities for palliative care, including specialist palliative care, as they consider appropriate for meeting the reasonable requirements of the people for whom they have responsibility'. Many see this, along with the significant and welcome resource provided to hospices by NHS England throughout the Coronavirus pandemic, as a step towards 'fully funded' hospice care. Our hospice has worked hard to develop relationships and build connections over many years, which has resulted in an NHS contribution towards our costs well above the national average. We have a mature relationship with CCG commissioners and other local statutory providers and very much see our role as a partnership that aims to improve care for all, regardless of who the provider of that care is. Methods/Results/Conclusions: Our presentation will discuss the risks and benefits of hospice care that is 'fully funded' through statutory means and argue that, to achieve real sustainability, hospices need to invest resource, time and skills in commissioner and partner provider relationships in the way that they invest in other aspects of income generation. We will also argue that as independent hospices, our charitable status and independence enables us to remain connected to our communities, and that as precious community assets, not being fully funded allows innovation beyond what the political paymasters of the day specify. In remaining so, we can continue to act as leaders of compassionate care in the integrated care systems and work with partners to improve end of life care for all, acting creatively and investing in new areas to change how we die. The session aims to be provocative, recognising that all hospices have their own challenges and opportunities and that there remains a place for diversity of funding across the sector.